INVITRO ANTIOXIDANT ACTIVITY AND HPTLC ANALYSIS OF WITHANIA SOMNIFERA - Gupta Maheshkumar K2, *Makhija Manju1 (Journal of Biomedical and Pharmaceutical Research, 2014)
Withania somnifera is a well known medicinal plant having wide range of medicinal properties. HAEWS, MEWS and AEWS were comparatively standardized for the content of Withanolide D by HPTLC. All the samples were screened for the possible in-vitro antioxidant activity for 1,1-diphenyl-2-picryl-hydrazil (DPPH.) free radical scavenging, hydrogen peroxide scavenging, flavonoid content, polyphenolic contents, and lipid peroxidation effects. The Withanolide D content of HAEWS, MEWS and AEWS was found to be 0.103, 0.067, and 0.036% (w/w) respectively. The Polyphenol and flavonoid content of HAEWS was found to be 35.51, 17.68 (w/w) respectively.  All the tested samples showed marked antioxidant activity in which HAEWS showed prominent activity. HAEWS showed significant (p<0.01) (DPPH) free radical scavenging (67.38%), hydrogen peroxide scavenging (61.05%) and lipid peroxidation (63.86%) , reducing power (0.93%) at the concentration of 1000mg/ml. These various antioxidant activities were compared to standard antioxidant such as ascorbic acid.  Key words: Withania somnifera, HPTLC, antioxidant, radical scavenging. Abbreviations:HAEWS: Hydroalcholic extract of Withania somniferaMEWS: Methanolic extract of Withania somniferaAEWS: Aqueous extract of Withania somniferaDPPH: (1,1-Diphenly-2-picryl-hydrazil)